BASIC PREDICTORS OF POST-TRAUMA STRESS DISORDER FORMATION AMONG COMBATANTS - Kazmirchuk А.P.; Lashin, O.I.; Druz О.V.; Chernenko І.O. (World of Medicine and Biology, 2020)
In the present work, the authors identify predictors of the post-traumatic stress disorder (PTSD) formation among combatants. The study results include: a) tendency to express negative feelings through the form and content of verbal answers; b) unstable balance between the simultaneous desire for truthfulness and aggravation of PTSD symptoms, which provides a PTSD prognosis at the level of ΣDC = 20.59> 20; c) combination of high level anxiety with a normal level of spontaneity, which ensures a PTSD forecast of ΣDK = 15, 82> 13. Thus, an important component of the rehabilitation for combatants with PTSD is the creation of an appropriate therapeutic environment based on a patient-centered approach to potentiate the psychological, psychotherapeutic work aimed at restoring the relations between combatants, at the level of micro- and macro-environment.